Analysis of Drainage Channel Dimensions at Villa Terracotta in Badung Regency - Soriarta, I Ketut; Putra, I Putu Dwikarna (Jurnal Ilmiah Telsinas, 2026)
The development of Villa Terracotta in Ungasan Village, South Kuta District, Badung Regency faces potential water ponding problems due to a drainage system that does not conform to the existing topographic conditions. This study aims to evaluate drainage capacity and design an appropriate channel dimension to prevent overflow. The research applies a quantitative approach using hydrological and hydraulic analysis. Design rainfall was determined using the Gumbel distribution after conducting Smirnov–Kolmogorov and Chi-square goodness-of-fit tests. Rainfall intensity was calculated using the Mononobe method, while hydraulic performance of the drainage system was simulated using the EPA-SWMM model. The study area covers 0.27 ha with elevations ranging from 109.5 m to 111.5 m above sea level. The calculated rainfall intensity ranges from 24.84 mm/h for a 2-year return period to 54.78 mm/h for a 50-year return period with a rainfall duration of 1 hour. Simulation results show that the downstream channel has a maximum flow depth of 0.43 m. A channel dimension of 0.30 m width and 0.55 m height produces a freeboard of 27.9%, which falls within the recommended safety range of 5%–30%, indicating that the designed channel is hydraulically safe against overflow.